2011
DOI: 10.1002/pon.1760
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among family carers of oesophageal cancer survivors: the role of illness cognitions and coping

Abstract: Objective: The research aimed to determine the extent to which illness cognitions and coping explain psychological distress (fear of cancer recurrence, anxiety and depression symptoms) among family carers of survivors of oesophageal cancer.Methods: Carers of patients registered with the Oesophageal Patients' Association in the UK were mailed a questionnaire booklet containing questions about medical and demographic variables, the Illness Perception Questionnaire‐Revised, the Cancer Coping Questionnaire, the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 37 publications
5
49
0
2
Order By: Relevance
“…perception of the consequences after a consideration of the resources available to cope with these consequences. This observation may help to explain why the majority of research in this area has found no mediating role for coping in the explanation of psychological wellbeing (Hagger & Orbell, 2003;Dempster et al, 2011b).…”
Section: Discussionmentioning
confidence: 90%
“…perception of the consequences after a consideration of the resources available to cope with these consequences. This observation may help to explain why the majority of research in this area has found no mediating role for coping in the explanation of psychological wellbeing (Hagger & Orbell, 2003;Dempster et al, 2011b).…”
Section: Discussionmentioning
confidence: 90%
“…9 International research bring that women caregivers have higher levels of depression than men who exercise the same role. 10,11 Another study showed that male caregivers of people with cancer had a degree of welfaresignificantly higher than the female caregivers. 5 However, in this study, the welfare indices showed no statistically significant difference in relation to gender.…”
Section: Discussionmentioning
confidence: 99%
“…Illness perceptions and coping strategies have been found to explain between 35 and 49 % of the variance in the psychological distress of those caring for patients with oesophageal cancer [14]. Illness perceptions explained the greatest proportion of this variance, particularly perceptions of consequences, personal control, and understanding of the cancer.…”
Section: Introductionmentioning
confidence: 98%